MORPHOLOGICAL FEATURES OF THE PLACENTA AND VAGINAL MICROBIOCENOSIS IN WOMEN WITH PREMATURE BIRTH - Татьяна Юрьевна Марочко (Мать и дитя в Кузбассе, 2019)
Objective – to assess the morphological features of the structure of the placenta and the state of the microflora of the vagina and placenta in women with preterm birth.